Coordinating ecological restoration options analysis and risk assessment to improve environmental outcomes. (15th September 2015) - Kapustka, Lawrence A; Bowers, Keith; Isanhart, John; Martinez‐Garza, Cristina; Finger, Susan; Stahl, Ralph G; Stauber, Jenny
ABSTRACT: Ecological risk assessment as currently practiced has hindered consideration of ecosystem services endpoints and restoration goals in the environmental management process. Practitioners have created barriers between procedures to clean up contaminated areas and efforts to restore ecosystem functions. In this article, we examine linkages between contaminant risk assessment approaches and restoration efforts with the aim of identifying ways to improve environmental outcomes. We advocate that project managers and other stakeholders use an ecological planning framework, with restoration options included upfront in the risk assessment. We also considered the opportunities to incorporate ecosystem services as potential assessment endpoints in the Problem Formulation stages of a risk assessment. Indeed, diverse perspectives of stakeholders are central to understand the relevance of social, cultural, economic, and regional ecology as influences on future use options for the landscape being restored. The measurement endpoints used to characterize the existing ecological conditions for selected ecosystem services can also be used to evaluate restoration success. A regional, landscape, or seascape focus is needed throughout the risk assessment process, so that restoration efforts play a more prominent role in enhancing ecosystem services. In short, we suggest that practitioners begin with the question of "how can the ecological risk assessment inform the decision on how best to restore the ecosystem?" Integr Environ Assess Manag 2016;12:253–263. © 2015 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of SETAC Key Points: Limitations of ERA as currently practiced have hindered consideration of ecosystem services endpoints and restoration goals in the environmental management process. Ecological restoration options should be brought to the front of the problem formulation phase of the risk framework. A regional, landscape, or seascape focus is needed throughout the risk assessment process so that restoration efforts play a more prominent role in enhancing ecosystem services (e.g., provision of habitat).